The Preventive Effect of Biochanin A on Bone Loss in Ovariectomized Rats: Involvement in Regulation of Growth and Activity of Osteoblasts and Osteoclasts. (21st February 2013) - Su, Shu-Jem; Yeh, Yao-Tsung; Shyu, Huey-Wen
Abstract : Biochanin A (BCA) is a major isoflavone abundant in red clover ( Trifolium pretense ). The protective effect of BCA on bone loss in an ovariectomized (OVX) animal model has never been clarified. The objective of this study was to investigate the biological effects of BCA on bone loss in OVX rats in vivo and on the development of osteoblasts and osteoclasts in vitro . Ovariectomy resulted in a marked increase in body weight and a decrease in femoral bone mineral density and trabecular bone volume that was prevented by BCA or 17 β -estradiol (E2) treatment. However, an increase in uterine weight was observed in E2-treated OVX rats, but not in response to BCA treatment. Treatment with BCA increased the mRNA expression of osterix, collagen type I, alkaline phosphatase (ALP), and osteocalcin and decreased the mRNA expression of tartrate-resistant acid phosphatase (TRAP) and the receptor activator of nuclear factor- κ B ligand (RANKL)/osteoprotegerin (OPG) ratio in the femur of OVX rats. Treatment with BCA or E2 prevented the OVX-induced increase in urinary deoxypyridinoline (DPD) and serum tumor necrosis factor α (TNF- α ) and interleukin-1 β (IL-1 β ). In vitro, BCA induced preosteoblasts to differentiate into osteoblasts and increased osteoblast mineralization. BCA inhibited preosteoclasts and osteoclast proliferation and decreased osteoclast bone resorption. These findings suggest that BCA treatment can effectively prevent the OVX-induced increase in bone loss and bone turnover possibly by increasing osteoblastic activities and decreasing osteoclastic activities.